The socio-economic impact of ENSO-related climate variability on rural households in Central Sulawesi, Indonesia - Alwin Keil (PANGAEA, 2007)
Data were collected in in the province of Central Sulawesi, Indonesia, in the villages of Maranata, Sidondo II, Pandere, Sintuwu, Berdikari, Nopu (Bulili), Bolapapu, and Tomado. They include information on El Nino-related drought periods experienced by 228 randomly selected farm households, and associated ex-ante mitigation and ex-post coping measures.